Modeling of the mechanical behavior of composite at different relative humidities - Naceri, A. (Проблемы прочности, 2009)
The moisture diffusion and mechanical response in shear of a laminate constituted of 12 layers of glass fabric fiber/epoxy resin were evaluated. The experimental analysis of the moisture absorption of the specimens conditioned at different relative humidities, 0, 60, and 96% RH at 60°C was to determine the two parameters characteristic of the Fick diffusion law (the diffusion coefficient D and the maximum quantity of water of saturation Mm) which admits the reversibility of the phenomenon. The analysis of the mechanical response in shear of the specimens oriented at 45° tested in uniaxial tension at constant imposed displacement rates, has permitted to show that the influence of the moisture concentration for the composite is very important at 96% RH. The proposed simple model permits to specify the influence of water absorption on the mechanical behavior in shear. Для дванадцятишаруватого ламіната з матрицею з епоксидної смоли і скловолокон досліджено закономірності абсорбції вологи і механічної поведінки в умовах зсуву. Експериментальні дослідження абсорбції вологи зразками з ламіната за різних значень вологості повітря (0, 60 і 96%) при температурі 60°C дозволили визначити два параметри (коефіцієнт дифузії D і максимальну кількість вологи при насиченні M m), що характеризують закон дифузії Фіка, який припускає зворотність процесу. Аналіз механічної поведінки при зсуві, що забезпечується одновісним розтягом ламіната з волокнами, орієнтованими під кутом 45° до осі розтягу, при постійних швидкостях переміщення показав, що при вологості 96% концентрація вологи в композиті грає особливо важливу роль. Запропоновано просту модель, яка дозволяє описати вплив абсорбції вологи на механічну поведінку ламіната при зсуві. Для 12-слоистого ламината с матрицей из эпоксидной смолы и стекловолокон исследованы закономерности абсорбции влаги и механического поведения в условиях сдвига. Экспериментальные исследования абсорбции влаги образцами из ламината при различных значениях влажности воздуха (0, 60 и 96%) при температуре 6WC позволили определить два параметра (коэффициент диффузии D и максимальное количество влаги при насыщении Mm), характеризующих закон диффузии Фика, который предполагает обратимость процесса. Анализ механического поведения при сдвиге, обеспечиваемом одноосным растяжением ламината с волокнами, ориентированными под углом 45° к оси растяжения, при постоянных скоростях перемещения показал, что при влажности 96% концентрация влаги в композите играет особенно важную роль. Предложена простая модель, позволяющая описать влияние абсорбции влаги на механическое поведение ламината при сдвиге.